The Development of GIS Database for Blackspot Accident Area Affected by Day And Night Time - Hamid, Fatin Zawani; M. B, Saifullizan (Recent Trends in Civil Engineering and Built Environment, 2021)
Road accidents are one of the largest contributors to human deaths in Malaysia and are caused by a combination of factors which include the weather, road engineering, vehicle characteristics, as well as driver performance and actions. This paper aimed to (i) to identify factors causing of blackspot traffic accident area of the route during daytime and nighttime (ii) to analyze road accident data using Geographic Information System (GIS) for the black spot area. Besides, with the advanced aid of technology nowadays, a Geographic Information System (GIS) was being recognized as an excellent system that can be used as an advanced tool in the field of transportation. The determination of the blackspot area needs to be traced and the factor causing need to be identified before all the data being carried out by using the GIS system. Thus, by the end of this research, hopefully, this study can identify and prioritize the accurate accident-prone points (blackspots) area so the factor causing an accident can be detected with spatial information using GIS and the quantity of road accident hope can be reduced when the prediction of safety can be measured and monitored with the help of GIS database